'Such Misconducts Don't Make a Good Ranger': Examining Law Enforcement Ranger Wrongdoing in Uganda. (16th October 2014) - Moreto, William D.; Brunson, Rod K.; Braga, Anthony A.
Abstract : Wildlife crime has been recognized to be an important topic of study by criminologists in recent years. Prior research has highlighted the detrimental impact of corruption on conservation-related issues. Law enforcement rangers are often the primary protectors of protected areas and wildlife. Yet, like other law enforcement agents, they are not immune to misconduct and corruption. The present study offers an in-depth examination of rangers' experiences with and perceptions of wrongdoing in a specific Ugandan protected area. Findings indicate that ranger wrongdoing is driven by a myriad of factors and manifests in various ways. These findings have implications for the understanding and prevention of ranger misconduct.